2019
DOI: 10.3389/fphar.2019.01443
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Validation of the Protective Effects of Aqueous Bark Extract of Terminalia arjuna (Roxb.) on Isoproterenol-Induced Cardiac Hypertrophy in Rats

Abstract: Cardioprotection by Terminalia arjuna During Stress Signaling Kumar et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…Arjunakwaatha and Arjunasheetha contain various antioxidant components due to their being prepared from bark of Terminalia arjuna (TA). 22 Giri et al found that an aqueous extract of TA lowered urea and creatinine levels in rats with paracetamol-induced CKD, 13 which matched the results of the current investigation. Arjunakwaatha and Arjunasheeta improved kidney tissue antioxidant capacity and reduced the concomitant oxidative stress, as indicated by elevations in GSH levels and SOD activity, an increase in CAT activity, and the decreases in the tissue levels of MDA compared to those of kidney injury rats (Figure 8).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Arjunakwaatha and Arjunasheetha contain various antioxidant components due to their being prepared from bark of Terminalia arjuna (TA). 22 Giri et al found that an aqueous extract of TA lowered urea and creatinine levels in rats with paracetamol-induced CKD, 13 which matched the results of the current investigation. Arjunakwaatha and Arjunasheeta improved kidney tissue antioxidant capacity and reduced the concomitant oxidative stress, as indicated by elevations in GSH levels and SOD activity, an increase in CAT activity, and the decreases in the tissue levels of MDA compared to those of kidney injury rats (Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…[18][19][20] Excess paracetamol causes the overproduction of reactive oxygen species (ROS) in kidney tissue by altering the oxidant-antioxidant balance with an increase in lipid peroxidation. 22 In the study, we observed that paracetamol treated rats were associated with increased MDA levels and a significant decrease in SOD, CAT, and GSH activity. The SOD-CAT-GSH renal antioxidant enzyme axis maintains the oxidant-antioxidant balance in the normal kidney where disbalance of that axis indicates kidney injury 20 (Figure 8).…”
Section: Discussionmentioning
confidence: 83%
“…The accumulation of ROS or antioxidant potential in efficiency are probably TBARS levels enhanced in plasma in DMBA treated hamsters. Lowered the enymatic and nonenzymatic antioxiants by remove excessive formation of antioxidant 46,47 . Orally treated TQ/Ca‐alg‐PVA to DMBA administered hamsers showed regained the level of plasma lipid peroxidation and anti‐oxidants capabilities.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, several naturally occurring compounds have been shown to alleviate the hypertrophic phenotype through suppression of oxidative stress. For instance, the pulp powder extracted from Musa balbisiana (banana) [90], the lowbush blueberry extract (Vaccinium angustifolium) [91], the aqueous extract of the Terminalia arjuna bark [92] and pomegranate juice [93] have been associated with reduction in heart weight, fibrosis, inflammation and oxidative stress. In addition to supressing cardiac hypertrophy, these compounds have been reported to exert beneficial effects across several pathologies suggestive of pleiotropic function.…”
Section: Therapeutic Strategies For Attenuating Oxidative Stress Anti...mentioning
confidence: 99%